PERLINDUNGAN HUKUM TERHADAP PEKERJA ANAK DI PASAR UMUM KINTAMANI KABUPATEN BANGLI - Ni Putu Rasningsih*; I Made Dedy Priyanto (Jurnal Tengkhiang, 2022)
The aim of this study is to provide an overview of the gap between legal norms and reality in society, especially in the Kintamani Public Market. The research method used is a type of empirical legal research. The approach uses a statutory approach and a fact approach. The nature of this research is descriptive in nature. Sources of data used are primary data and secondary data. Primary data includes data obtained from interviews at the research location, while secondary data comes from legislation and literature, journals and internet media. The data analysis technique uses a qualitative descriptive analysis technique. The results of this study are the factors that cause children to become workers in the Kintamani Public Market, there are external factors and internal factors. External factors include economic factors, parents, and the environment. While the internal factor is the desire of the child himself to work. This desire originates from the boredom experienced by children when they stay at home, because if they stay at home, there is a lot of work to be done. Then, legal protection for child labor at the Kintamani Public Market is carried out with reference to the rights and obligations of child labour. However, the implementation of this legal protection has not been effective because it is still experiencing obstacles in the form of a lack of socialization from the Regional Government and the desire of traders to prioritize provide-oriented so that wages child labor can be suppressed and traders get the maximum profit.